Editorial: von Willebrand factor and CRP levels may predict survival in liver cirrhosis. Issue 11 (June 2018) - Merli, M.; Di Gregorio, V.
Abstract : Linked Content This article is linked to Mandorfer et al papers. To view these articles visithttps://doi.org/10.1111/apt.14522 andhttps://doi.org/10.1111/apt.14624 .